Fibroblast growth factor receptors and their inhibitors in preclinical models of breast cancer and bone metastasis - Kähkönen, Tiina (fi=Turun yliopisto|en=University of Turku|, 2019)
Advanced, metastatic stages of breast cancer are associated with high morbidity and mortality, and there is a need to establish a proof-of-concept for novel compounds that can change this scheme. Fibroblast growth factors and their receptors (FGFRs) are altered in about 18% of breast cancers, resulting in malignant growth and resistance to conventional therapies. During the past few years many compounds inhibiting the activity of FGFRs have been discovered but not yet approved for breast cancer. In this study, the effects of pharmacological inhibition of FGFRs by FGFRselective and non-selective inhibitors on proliferation, apoptosis, migration, invasion and angiogenesis were evaluated by different in vitro and in vivo models, and in ex vivo explant cultures using clinical breast cancer tissue specimens. FGFR1 was a major regulator of breast cancer growth. FGFR selective inhibitors were most effective in FGFR-amplified cells. FGFR inhibitors decreased proliferation of breast cancer cells, which was the major cause of growth inhibition.Migration and invasion were also inhibited, and induction of apoptosis was observed in certain experimental models. FGFR inhibitors decreased tumor growth in subcutaneous models, and also in a model mimicking growth of bone metastases in vivo. FGFR inhibitors did not have any harmful effects on healthy bone or on boneforming osteoblasts. In conclusion, FGFR inhibitors showed many anti-tumor effects in breast cancer. Many of these compounds are currently being evaluated in clinical trials.

Edennyt, etäpesäkkeitä muodostava rintasyöpä lisää merkittävästi kuolleisuutta potilaissa, ja uusia tehokkaita lääkkeitä sen hoitamiseen tarvitaan kipeästi. Noin 18 %:ssa rintasyövistä havaitaan fibroblastikasvutekijöissä ja niiden reseptoreissa (fibroblast growth factor receptor, FGFR) geenimuutoksia, jotka johtavat syövän kehittymiseen ja lopulta lääkeresistenssiin. Viime vuosina on kehitetty useita FGFR:iin vaikuttavia lääkeaineita, mutta niitä ei ole vielä hyväksytty rintasyövän hoitoon. Tässä tutkimuksessa selvitettiin FGFR-epäselektiivisten sekä FGFR-selektiivisten pienimolekyylisten inhibiittoreiden vaikutuksia solujen jakautumiseen, solukuolemaan, liikkumiseen, tunkeutumiseen ja verisuonten muodostukseen. Tutkimuksessa käytettiin erilaisia solu- ja tuumorimalleja, sekä potilaista saatuja rintasyövän kudosviljelmiä. Tutkimuksessa FGFR1 osoittautui voimakkaaksi rintasyövän säätelijäksi. FGFR-selektiiviset inhibiittorit olivat erityisen tehokkaita malleissa, joissa oli FGFR geenimuutoksia. FGFR-inhibiittorit hidastivat ensisijaisesti syöpäsolujen jakautumista ja siten syövän kasvua. Lisäksi inhibiittorit vähensivät syöpäsolujen liikkumista ja tunkeutumista, sekä lisäsivät solukuolemaa tietyissä tutkimusmalleissa. FGFR inhibiittorit vähensivät syövän kasvua myös primäärituumorimallissa, sekä mallissa, jossa syöpäsolut kasvoivat luussa, vaikuttamatta kuitenkaan terveeseen luuhun tai luuta muodostaviin soluihin. Yhteenvetona voidaan todeta, että FGFR inhibiittoreilla on monia syövän kasvua estäviä vaikutuksia. Tällä hetkellä näiden inhibittoreiden tehoa arvoidaan kliinisissä kokeissa.